MENINGKATKAN PENDAPATAN UMKM DENGAN PELATIHAN DIGITAL MARKETING DI MASA PANDEMI COVID-19 DI RT.011 RW.011 PONDOK UNGU PERMAI - Lingga Putri Anisti; Mita Widyastuti; Dila Novita (Universitas Islam 45 Bekasi, 2022)
Real Work Lectures are part of the Tri Dharma of Higher Education which specifically carries out community service. This Real Work Lecture was held at RT 011 RW 011 in the Pondok Ungu Permai area, North Bekasi District, Central Kaliabang Village, with the aim of providing training skills for community approaches and forming attitudes and personalities that are always sensitive to the problems faced by the community. The method used in this service is public education and training by assisting MSME actors in using social media such as Instagram and other applications to keep their business running during the Covid-19 pandemic. The results of this outreach program carried out in the neighborhood where I live, namely on Rt.011 Rw.011 went smoothly and of course there were obstacles that were passed to carry out and run the program. The local residents were very enthusiastic and participated in the activities carried out.